A review of comparison between the traditional catalyst and zeolite catalyst for ammonia-selective catalytic reduction of NOx. (15th July 2023) - Sunil Kumar, M; Alphin, MS; Manigandan, S; Vignesh, S; Vigneshwaran, S; Subash, T
Highlights: deNOx efficiency was more influenced by Zeolite catalysts than traditional catalysts (Vanadium, Manganese, Cerium, etc.) in the NH3 -SCR activity. Among zeolite catalysts, Cu-doped and Fe-doped zeolite catalysts exhibit excellent deNOx efficiency in lower and higher operating temperatures respectively. The parameters such as GHSV, operating temperature window, and doping percentage exhibit the catalyst's performance for NOx in ammonia-selective catalytic reduction. Abstract: Emission plays a vital role in the pollution of air and influences various effects on the living beings in the environment, including significant health effects for living beings. Therefore, several emission control measures were implemented to achieve a pollution-free environment. Selective Catalytic Reduction (SCR) is one of the post-combustion technologies predominantly used in an internal combustion engine to reduce the percentage of oxides of Nitrogen (NOx ) emissions in the exhaust gases. This review covers various types of catalysts used in SCR for the reduction of NOx emissions, such as metal-based catalysts (Vanadium, Manganese, Titanium, and Cerium) and zeolite-based catalysts, providing an insight into the performance along with the effects of characteristics behaviour of each catalyst such as GHSV, efficiency for various temperature window, percentage doping, and NOx conversion efficiency. The review concludes zeolite catalyst exhibits excellent deNOx efficiency, which 2 to 4 wt% doping of Cu shows deNOx around 95%, and doping of Fe widens the operating window temperature.